The Role of Non-Verbal Means in Teaching - Sobirova Nargiza Numonjonovna; Ibragimova Extiyotxon Ismailovna; Kasimova Guljaxon Mahmudovna (Genius Journals, 2023)
The article is devoted to non-verbal communication and it’s role in teaching. It is known that before the written form of language human beings started to communicate orally and the basis of oral speech was non-verbal means. In this article the definition of nonverbal communication was given, means of non-verbal communication were counted and the role of non-verbal means in teaching languages was explained.
Keywords: non-verbal communication; language; teaching